Biotechnological advances in enhancing soybean oil quality for human health and food industry applications - Da Rosa, Juliana; Marin, Daniel Rockenbach; Vieira da Silva, Angela Maria; De Souza, Enya Maria Gois; Rech, Elibio Leopoldo; Nepomuceno, Alexandre Lima; Mertz-Henning, Liliane Marcia (Frontiers in Food Science and Technology, 2025)
Soybean oil is a major source of vegetable oil for human consumption. Conventional soybean oil contains high levels of polyunsaturated fatty acids, and partial hydrogenation was historically used to improve oxidative stability. However, hydrogenation generates trans fatty acids, which are harmful to cardiovascular health and have therefore been banned or restricted by health regulatory agencies in several countries. Currently, techniques such as oil blending and interesterification are employed, although these approaches increase costs and highlight the need for improved soybean oil quality. Recent advances in biotechnology have enabled the development of genetically modified soybean cultivars aimed at improving the nutritional profile of soybean oil for both human consumption and food industry applications. Key advancements include the development of soybean cultivars with high-oleic acid content, which increases oxidative stability; high-linolenic acid content, which enhances nutritional and functional properties; and low-palmitic acid content, which reduces saturated fatty acid levels and contributes to healthier oils. This review explores a range of biotechnological strategies to optimize soybean oil quality, including genetic engineering, RNA interference, and gene editing, which are employed to modify key metabolic pathways responsible for oil biosynthesis. These innovations not only enhance the health benefits of soybean oil, such as reducing cardiovascular disease risk, but also improve its oxidative stability for high-temperature cooking and extended shelf life.